Development of a novel engineered stone containing a CuO/SiO2 nanocomposite matrix with biocidal properties. (11th October 2021) - Zarzuela, Rafael; Almoraima Gil, M.L.; Carretero, Jesus; Carbú, María; Cantoral, Jesús M.; Mosquera, María J.
Graphical abstract: Highlights: Quartz particles are integrated within the silica xerogel matrix after curing at room conditions. Excess water during mixing leads to cracks in the matrix and poor matrix-quartz cohesion. The stones are scratch-resistant (Mohs hardness 7) and their impact resistance is higher than clay floor tiles. CuO increases rigidity of the SiO2 xerogel matrix, but the stones have a higher porosity. The CuONPs in the xerogel inhibit fungal growth and cause damage to the spores. Abstract: Building materials decay is caused by the combination of chemical, physical and biological aspects. Therefore, the development of innovative multifunctional building materials is an alternative to reduce their impact. This can be achieved by post-treatments or by direct changes in the fabrication of synthetic materials, such as engineered stone. The aim of this work is to develop a new type of engineered stone by using a CuO/SiO2 nanocomposite matrix, synthetized via sol–gel, as a binder and quartz particles of different grain size as aggregate. The use of a sol–gel route allows creating an amorphous SiO2 structure chemically compatible with the quartz aggregates, while CuO nanoparticles are added for their biocidal properties. The new materials present anti-fungal properties against yeast and Aspergillus carbonarius spores, a high surface hardness, thermal resistance and an appropriate impact resistance for their use in flooring and claddings, although their mechanical strength is overall lower than a resin-matrix engineered stone. The proportion of CuO in the matrix and water content modify the sol–gel kinetics and quartz sedimentation, which have an impact on the structure and mechanical properties.